Overcoming the Therapeutic Limitation of Ocular Drug Delivery with the Help of Novel Drug Carriers - Shadab, Sumbul; Alam, Md. Aftab; Sharma, Pramod Kumar; Paliwal, Deepika (Current Nanomaterials, 2025)
One of the difficult areas of pharmaceutical research is the controlled delivery of drugs to the eye. The drainage of the solution, the quick turnover of the tears, and the diluting effects of lacrimation all contribute to a short drug contact time and poor ocular bioavailability with conventional systems. Drug delivery system design is also governed by the eye's anatomical barriers and its physiological conditions. To prevent retinal uptake of drugs given systemically, the blood-retinal barrier (BRB) has tight junctions that block drug entry. It has been discovered that conventional ophthalmic dosage forms can be avoided along with the problems they cause by using nanocarriers. There are a variety of nanosized carriers available for this purpose, including liposomes, niosomes, polymeric micelles, Nanocarrier-loaded gels, Solid Lipid Nanoparticles (SLNs), polymeric nanoparticles, and dendrimers. This review gives a resume of the different parts of ocular delivery, with a focus on nanocarrier-based strategies, such as delivery routes and the challenges and limits of making new nanocarriers.
Keywords: nanoparticle